Quantifying the effect of boat disturbance on bottlenose dolphin foraging activity. (January 2015) - Pirotta, Enrico; Merchant, Nathan D.; Thompson, Paul M.; Barton, Tim R.; Lusseau, David
Highlights: We use passive acoustic techniques to quantify boat disturbance on dolphin foraging. We develop a novel analytical procedure to account for noise masking. Boat presence, rather than noise, corresponded to a short-term reduction in foraging. The effect of boats depended on context, as well as number and type of boats. Our results can be used to inform impact assessments for future industrial developments. Abstract: Assessments of anthropogenic impacts on marine wildlife often concentrate on large-scale displacement. However, changes in the activity patterns of animals that do not flee could also affect their energy balance. Increasing boat traffic raises concerns for exposed marine mammals. Understanding risk perception is critical for effective mitigation and management, but it is hard to disentangle the effect of noise, physical presence of boats, and context. We used passive acoustic techniques to quantify how boat disturbance affected bottlenose dolphin foraging activity, and characterized the conditions influencing responses. To account for potential masking effects of boat noise on foraging vocalizations (buzzes), we developed a novel procedure to estimate the relationship between buzz detection probability and noise levels in particular 1/3 octave bands. Bayesian hierarchical modeling was then used to assess the effect of boat presence on buzz occurrence, as well as potential interactions with noise level, location, year, day, hour, dolphin group size, and boat type and number. Our results indicate that boat presence was associated with a short-term 49% reduction in foraging activity, but there was no relationship with noise level. Differences between sites and between years suggested a variable susceptibility depending on foraging conditions. This effect increased for increasing number of boats and depended on boat type. This is the first study conclusively showing that boat physical presence, and not just noise, plays a large role in disturbance.